Social and Economic Impact of Palm Oil Plantation For Local Communities in Kapuas Hulu District - Pether Sobian (Sekolah Pascasarjana Universitas Brawijaya, 2019)
Oil palm agribusiness opportunities have stimulated several investors to plunge into the oil palm plantation sector in Kapuas Hulu. The Kapuas Hulu Regency Government certainly hopes that the existence of an oil palm plantation company can contribute optimally to regional development and the welfare of the local community. This is inseparable from the assumption and expectations that oil palm plantations are strategic sectors that can have an economic impact on a chain basis. Therefore, these companies are expected to have a community development program (Community Development) as part of corporate social responsibility (CSR). Companies, in this case, must strive to actualize the potential that is already owned by the community through a community empowerment approach that emphasizes the importance of independent local communities as a system capable of organizing themselves. The establishment of oil palm plantation companies in Kapuas Hulu which are generally in rural areas certainly influences the social and economic life of the community around the location. The social impacts that occur can be in the form of changes in people's lifestyles such as patterns of production and consumption, value systems, norms, and beliefs. This is understandable given the intensity of interaction, interaction, and communication between the local community and the plantation and with other migrant communities sooner or later will affect the way of life, mindset, and patterns of social relations of the local community.